2018
DOI: 10.3390/jcdd5010014
|View full text |Cite
|
Sign up to set email alerts
|

Roles of A-Kinase Anchoring Proteins and Phosphodiesterases in the Cardiovascular System

Abstract: A-kinase anchoring proteins (AKAPs) and cyclic nucleotide phosphodiesterases (PDEs) are essential enzymes in the cyclic adenosine 3′-5′ monophosphate (cAMP) signaling cascade. They establish local cAMP pools by controlling the intensity, duration and compartmentalization of cyclic nucleotide-dependent signaling. Various members of the AKAP and PDE families are expressed in the cardiovascular system and direct important processes maintaining homeostatic functioning of the heart and vasculature, e.g., the endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 204 publications
(270 reference statements)
0
45
0
Order By: Relevance
“…Compartmentation is also essential to pick the correct target for phosphorylation. For protein kinase A – the closest homolog of cGKI - a number of AKAPs (for A k inase a nchoring p roteins) have been characterized which immobilize PKA into scaffolds of signaling complexes containing activators and substrates which are phosphorylated by PKA ( Torres-Quesada et al, 2017 ; Ercu and Klussmann, 2018 ). cGKI is expressed as two isoforms, termed α and β, that differ in their first ∼100 N-terminal residues.…”
Section: Discussionmentioning
confidence: 99%
“…Compartmentation is also essential to pick the correct target for phosphorylation. For protein kinase A – the closest homolog of cGKI - a number of AKAPs (for A k inase a nchoring p roteins) have been characterized which immobilize PKA into scaffolds of signaling complexes containing activators and substrates which are phosphorylated by PKA ( Torres-Quesada et al, 2017 ; Ercu and Klussmann, 2018 ). cGKI is expressed as two isoforms, termed α and β, that differ in their first ∼100 N-terminal residues.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, compartmentalization of PDEs further contributes in shaping cAMP microdomains by defining molecular barriers for cAMP diffusion [30,32]. Thirdly, organization of macromolecular signaling complexes containing ACs, PDEs, PKA, and its physiological substrates by a family of scaffolding proteins named A-kinase anchoring proteins (AKAPs), ensures spatiotemporal regulation of cAMP signaling events [31,33,34].…”
Section: The Functional Role Of Camp Signaling In Cardiac Fibroblastsmentioning
confidence: 99%
“…In the heart, AKAPs have been shown to regulate multiple physiological responses including cardiac contraction, rhythm and energy production as well as pathological functions linked to the development of arrhythmias, cardiac hypertrophy, fibrosis, and heart failure [7,141,142]. Several studies indicate that altering AKAP expression and signaling in cardiomyocytes can significantly impact their ability to survive cardiac stress and consequently influence replacement fibrosis [33,140,[143][144][145]. Since these results have been extensively reviewed in recent years, in the next paragraphs we will mainly focus on recent findings highlighting the role of AKAP signaling in cardiac fibroblasts.…”
Section: A-kinase Anchoring Proteinsmentioning
confidence: 99%
“…AKAPs are distinguished by their ability to bind cyclic adenosine monophosphate (cAMP)‐PKA at focal points within the cell to ensure the integration and processing of multiple signalling pathways . AKAP150 is an AKAP5 gene product that was first identified as a scaffolding protein predominantly expressed in the cerebral cortex that anchored the RII regulatory subunit of PKA to post‐synaptic densities . However, abundant data have shown that AKAP150 is important in the nervous system in functions such as neuron excitability and neuroendocrine function .…”
Section: Discussionmentioning
confidence: 99%